The silence of stones - Westerson, Jeri (Westerson, Jeri. Crispin Guest novels, 2015)
"London, 1388. When the mythical Stone of Destiny disappears from the throne of England during mass in Westminster Abbey, the populace takes it as a sign to side with King Richard II's rebellious barons. The last thing the king needs is for his authority to be put in question, especially after his army suffers a crushing defeat against a Scottish uprising. Desperate, Richard calls in Crispin Guest to find the missing stone. And to ensure that he will do the deed, the king imprisons Jack Tucker and orders Crispin to find the stone before Parliament convenes in three days' time--or Jack will hang for treason."--